The prevalence of vertigo among high school students and an evaluation of quality of life - Saglan, Ramazan; Goktas, Saniye; Emiral, Gulsum Ozturk; Unal, Egemen; Arslantas, Didem; Unsal, Alaettin (International Journal of Research in Medical Sciences, 2020)
Background: The purpose of the study is to determine the prevalence of vertigo among secondary and high school students, to examine the variables thought to be related and to evaluate the quality of life. Methods: This study was carried out between 1st November-30th December 2016 on secondary and high school students in Beylikova and Sivrihisar counties which is located at the research area of the Department of Public Health Eskisehir Osmangazi University. Those who had dizziness within the last three months have been assumed as having vertigo. Visual Analog Scale has been used in order to evaluate the severity of vertigo. The life quality of children has been evaluated through Quality of Life Scale (QoL) for Children. Results: The study group has been composed of 911 males (46.5%) and 1.047 females (53.5%). The prevalence of vertigo has been determined as 30.8%. The most common concomitant symptoms of students are headache (22.6%), staggering while walking (15.8%), and tinnitus (10.3%).It has been found that the QoL of students having complaints of vertigo is lower than that of those not having complaints of vertigo. The most common type of vertigo within the study group has been Orthostatic Dizziness (70.0%). There has been no correlation between types of vertigo and QoL; however, when the severity of vertigo is considered, it has been found within our study group that the QoL of the students having mild vertigo is higher than that of those having moderate or higher severity of vertigo(p<0.05. Conclusions: Vertigo is one of the most common symptoms among children and adolescents and may result from many factors. It may be useful to carry out screening with the purpose of early diagnosis and treatment parentheses, direct diagnosed cases to specialist physicians and organize events to create awareness. More comprehensive studies are needed to reveal the relationship between vertigo and QoL.